Hyperbolic discounting and the Phillips curve - Liam Graham; Dennis J. Snower (Institute for the Study of Labor (IZA), 2008)
Using a standard dynamic general equilibrium model, we show that the interaction of staggered nominal contracts with hyperbolic discounting leads to inflation having significant long-run effects on real variables.
urn:nbn:de:101:1-2008050232
Keywords: E20; 330; Inflation; unemployment; Phillips curve; nominal inertia; monetary policy; dynamic general equilibrium; Phillips-Kurve; Lohnrigidität; Dynamisches Gleichgewicht; Geldpolitik; Theorie